Melioidosis in Adults at Chachoengsao Hospital - Aree, Wattana (Journal of Health Science of Thailand, 2018)
The retrospective descriptive study, analysed data on melioidosis in adults from January 2005 to December 2007 in Chachoengsao Hospital, in a province in eastern region of Thailand. The positive Burkholderia pseudomallei specimen culture (blood sputum, urine, pus etc.) was a diagnosis criteria in this study. The secondary source; medical records, chest film, ultrasound and laboratory test were reviewed for patient’s demographic data, illness time, underlying diseases, clinical data, medical treatments, outcome, complications, and mortality rate. During the study period, 46 melioidosis patients were from all admitted cases identified. These patients were, on average, 55.1 (SD 14.2) years old, 29 males and 17 females (1.7:1), 69.5 percent. were in the range of 40 – 70 years old. Most were reported from June to December and 10 patients (21.7%) lived in Sanam Chai Kate District. Eventhough 19.6 percent of all had no underlying diseases but the rest had underlying medical conditions or diseases: diabetes mellitus (45.6%), excess alcoholic consumption (13.0%), liver cirrhosis (10.9%), renal disease (8.7%), thalassemia (6.5%) and COPD (Chronic Obstructive Pulmonary Disease) (6.5%), respectively. More than half were bacteremia cases (63%). All of these melioidosis patients were classified by Wipada Chaowagul’s criteria into non-disseminated septicemic melioidosis (56.5%), disseminated septicemic melioidosis (6.5%), the localized melioidosis (34.8%) and the multifocal localized (2.2%). In all, 63 percent were treated by ceftazidime and 11 cases were undergoing operation. In the mortal group (14 cases; 30.4%) were septicemic melioidosis (10 cases) and the localized melioidosis (4 cases). Melioidosis was the health problem in every part of Thailand, not only in the northeast area. The mortality rate was high in severe bacteremia cases so rapid diagnosis and optimal treatments were the key success factors.